2020
DOI: 10.3390/mi11030323
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study of Microchannel Performance on Flow Maldistribution

Abstract: Miniaturized heat exchangers are well known for their superior heat transfer capabilities in comparison to macro-scale devices. While in standard microchannel systems the improved performance is provided by miniaturized distances and very small hydraulic diameters, another approach can also be followed, namely, the generation of local turbulences. Localized turbulence enhances the heat exchanger performance in any channel or tube, but also includes an increased pressure loss. Shifting the critical Reynolds num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, the passive control device can control the base pressure, which result in an improvement in the base pressure and mitigating the base drag. In addition, passive control is very effective and efficient whenever there is preferable pressure gradient at the nozzle exit [28,29]. The results demonstrated that presence of ring required increased inlet pressure for moving fluid through the nozzle as it increases the mean velocity and turbulence at the exit.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the passive control device can control the base pressure, which result in an improvement in the base pressure and mitigating the base drag. In addition, passive control is very effective and efficient whenever there is preferable pressure gradient at the nozzle exit [28,29]. The results demonstrated that presence of ring required increased inlet pressure for moving fluid through the nozzle as it increases the mean velocity and turbulence at the exit.…”
Section: Resultsmentioning
confidence: 97%
“…The uniform velocity distribution in parallel channels is essential for practical applications as velocity maldistribution may lead to an uneven heat exchange and an uneven product yield in the industrial production. 25 To solve this problem, the DW structure is adopted, in which the width of the flow channel section gradually reduces to achieve the same flow resistance in each branch. As shown in Figure 7b, the velocity distribution in all parallel flow channels of the DW structure is obviously more uniform.…”
Section: Effects Of Configurations Of the Heat Exchangementioning
confidence: 99%
“…It has become one of the most promising technologies to solve thermal management problems in various electronics with high power density, and has been successfully applied to electronic chips and laser devices. After that, a large number of scholars proposed many improvement methods, such as turbulence structure [6,7], secondary flow [8,9], pulse flow [10,11], nanofluid [12,13], surface modification [14], and rough surface [15,16], from the directions of discussing heat exchange law [17,18], improving heat dissipation efficiency [19,20], improving flow field and temperature uniformity [21,22], and reducing pressure drop [23,24].…”
Section: Introductionmentioning
confidence: 99%